The Effect of Role Playing Model in Improving Results and Learning Activeness in Learning Strategy Subject of Technology and Vocational Education - Yosi Nur Kholisho (RedwhitePress)
Learning outcome is a tool to measure the extent to which the students master the material taught by educators. Here, the learning process is a key of success in achieving educational goals. Thus, the students are expected to experience changes in terms of knowledge, skills, values and attitudes. One of the problems faced by educators in conducting effective learning processes in order to improve learning outcomes is how to increase students' interest in that learning material. In order to solve that problem, educators can use role playing learning model.Role Playing model is one of cooperative learning models, this learning model is done by growing the students’ imagination.This study aims at determining whether the role playing learning model can improve learning outcomes and students’ learning activeness in the subjects of learning technology and vocational education strategies. Based on the results of analysis, it was obtained the average score 65.5 before treatmen is given and 84.4 after treatment is given. Here, it can be concluded that the role playing learning model successfully improves student learning outcomes. In addition, the results of students’ activeness testing during the process of lecturing, it was found that Ha 2 is accapted. It means that there was an effect of the application of role playing learning models to student learning activeness